Pembelajaran Kitab Al-Mabadi Al-Fiqhiyyah Dalam Membentuk Karakter Religius Santri Di Pondok Pesantren Al-Munawwir Sangatta Selatan - Mega Ayu utamima; M. Abdul Rozak; Maratul Latifah; Sinta Silvia Melia; Ramlah Harniati hapsah; Eko Nursalim (STIT Syekh Muhammad Nafis Tabalong, 2022)
The goal of this research was to illuminate how students at Al-munawwir Islamic Boarding School, located in Sangatta Selatan, were affected by studying Al-Mabadi AlFiqhiyyah. This approach to research employs qualitative, descriptive methods. Purposeful sampling will be used to select research participants, and observation, interviews, and documentation will be used to collect data. Reducing and summarizing data, presenting findings, and drawing conclusions are all part of the data analysis process. Visualization and summarization of data. Using data triangulation and source triangulation to confirm the veracity of the collected information. Religious affiliation among students is supported by the results of this study. Congregational prayer and reading the wirid (prayer) afterward are clear signs of this. study of Salaf books and reading the Qur'an, the entire religious series is carried out in accordance with Islamic principles.